Management of acute metabolic crisis in TANGO2 deficiency: A case report - (:unkn) unknown (My University, 2023)
TANGO2 deficiency is a rare inborn error of metabolism, with distinct clinical features. The clinical presentations of TANGO2 deficiency are developmental delay, speech difficulties, intellectual disability, non-life-threatening paroxysmal neurologic episodes (TANGO2 spells), acute metabolic crises, cardiac crises, seizures and hypothyroidism. Patients may die in acute metabolic crises. Here we report our experience in the management of an acute metabolic crisis in TANGO2 deficiency. A 9-year-old patient diagnosed with TANGO2 deficiency was admitted with fever, fatigue, unable to walk. In follow up, encephalopathy, rhabdomyolysis and arrhythmia were detected. Vitamin B-complex was started. Our patient\"s mental status and rhabdomyolysis improved dramatically, and cardiac crises ended without Torsades de pointes, ventricular tachycardia and/or fibrillation or myocardial dysfunction. With this report, we aimed to show the effectiveness of vitamin B-complex in the management of acute metabolic crises.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Pediatrics, Perinatology and Child Health; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; arrhythmia; encephalopathy; rhabdomyolysis; TANGO2 deficiency; vitamin B-complex